The Impact of Awareness, Lifestyle and Halal Certification on The Buying Interests of MSME’s Halal Food Products in DKI Jakarta - Nur, Muhammad Rizky Taufiq; Fathoni, Muhammad Anwar; Sari, Lili Puspita (El-Barka, 2021)
The research aims to explain the impact of awareness, lifestyle, and halal certification on people’s buying interest in MSME’s halal food products in DKI Jakarta Province. To the best of researchers’ knowledge based on the previous articles, there are no research titles that discuss the three variables simultaneously regarding the influence on the buying interest. Therefore, this research has some aspect of novelty compared to previous studies. Quantitative method is used for research methods that refer to numerical data. The subjects for this research are 150 consumers of MSME’s halal food products in the DKI Jakarta Province. Primary data collection is used as a technical data collection. Primary data was acquired from the distribution of questionnaires to MSME halal food consumers. Meanwhile, the data analysis techniques used were descriptive statistical analysis, classical assumptions, multiple linear regression, and hypothesis. The findings of this study among the three variables are used, two only have a significant influence on the buying interest whereas the three variables together have a significant influence on the buying interest of MSME products. To increase the buying interest of halal food products for MSMEs in DKI Jakarta, factors that can be considered important are halal awareness and halal lifestyle, because both have a significant impact on the buying interest. This can be interpreted if the two variables are increase it will also increase the buying interest of MSME’s halal food products in DKI Jakarta. On the other hand, if the three variables are considered simultaneously it will have a significant influence on buying interest.